GLOBAL EXPERIENCE IN THE APPLICATION OF URBAN PLANNING ACTIVITY REGULATORY TOOLS TO INCREASE THE OFFER OF AFFORDABLE HOUSING - BILETSKYI, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the global experience of using tools for regulating urban planning activities to increase the supply of affordable housing and analyzes the possibility of its adaptation to the realities of Ukraine. Taking into account the lack of affordable housing, the need for which has increased many times, or even tens of times, as a result of military operations, taking into account the number of destroyed and damaged housing stock objects, to meet the demand for residential real estate, it is proposed to use the tools of urban planning to ensure the needs of affordable housing for the victims from military armed aggression. Such instruments include making special requirements for the developer to set aside a particular share of affordable housing during the construction of new housing facilities, which can be transferred to local self-government bodies for ownership by specific households at prices lower than market prices. Or the application of such requirements in the case of particular conditions. For example, if the building density of a land plot exceeds a specific value, then such a building must have at least 20% of social housing (by area or number of residential units). Two factors are essential in this direction: urban planning and housing policy. The research conducted through an expert survey confirmed that under modern conditions, the most significant influence on market development and demand for real estate has such factors as population incomes, interest rates on loans, and real estate prices as well as under martial law conditions came to the fore regional factors such as distance from the border, etc. With the help of data analysis, it was established that the availability of housing for people with an average or low-income level is carried out through the mechanisms of its acquisition to improve living conditions. This characteristic is part of the country’s economic system. Previously, housing availability was ensured at the state’s expense, but with the transition to a market economy and the war, the ways of acquiring housing expanded significantly but became inaccessible to most citizens. Today, housing affordability depends on the population’s ability to pay and housing prices on the market.